2019
DOI: 10.1136/jmedgenet-2019-106011
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous mutations inSPEF2induce multiple morphological abnormalities of the sperm flagella and male infertility

Abstract: BackgroundMale infertility due to multiple morphological abnormalities of the sperm flagella (MMAF) is a genetically heterogeneous disorder. Previous studies revealed several MMAF-associated genes, which account for approximately 60% of human MMAF cases. The pathogenic mechanisms of MMAF remain to be illuminated.Methods and resultsWe conducted genetic analyses using whole-exome sequencing in 50 Han Chinese probands with MMAF. Two homozygous stop-gain variants (c.910C>T (p.Arg304*) and c.3400delA (p.Ile1134S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 27 publications
2
52
0
1
Order By: Relevance
“…Previous studies have promulgated the significance of SPEF2 in spermatogenesis . An intronic insertion within the Spef2 gene resulted in aberrant splicing and caused immotile and malformed sperm tails in pigs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have promulgated the significance of SPEF2 in spermatogenesis . An intronic insertion within the Spef2 gene resulted in aberrant splicing and caused immotile and malformed sperm tails in pigs .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have shown that the MMAF phenotype is associated with genetic mutations. Previous studies revealed that mutations in DNAH1 (MIM: 603332), DNAH2 (MIM: 603333), AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), AK7 (MIM: 615364), CFAP251 (MIM: 618146), CEP135 (MIM: 611423), FSIP2 (MIM: 615796), ARMC2 (MIM: 611226), QRICH2 (MIM: 618304), SPEF2 (MIM: 610172), CFAP69 (MIM: 617949), CFAP43 (MIM: 617558) and CFAP44 (MIM:617559) could cause the human MMAF phenotype . However, more research is needed to reveal the etiology of the remaining 30%–40% of MMAF cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014, when MMAF was defined, studies have shown that mutations in genes associated with sperm flagellum development may lead to MMAF . Here, another candidate gene, CFAP65 , was identified in an infertile male with MMAF by WES.…”
Section: Discussionmentioning
confidence: 95%
“…The genetic basis of male infertility is still a work in progress, more than 4000 genes are expressed in germ cells during sperm production, and variations in these genes may hamper spermatogenesis . Recent studies of families with positive history related to male infertility have reported that mutations in cilia‐related genes are responsible for MMAF (eg, DNAH1 , CFAP43 , CFAP44 , CFAP69 , CFAP251 , QRICH2 , AK7 , CEP135 , FSIP2 , SPEF2 , TTC21A , ARMC2 , AKAP4 , CCDC39 ) . However, the known genetic defects can only explain ~60% of the individuals affected by MMAF …”
Section: Introductionmentioning
confidence: 99%